Accounting for change and innovativeness: organizational climate change or renewable organizational energy? / Helen Black - Black, Helen (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
This paper examines how understanding the current climate for change and innovativeness in an organisational unit can inform decision making, strategic management and future change initiatives to enhance innovativeness. Specifically, this study contributes to the growing literature with a focus on using management control systems in pursuit of innovation outcomes and assesses the current climate for change and innovativeness in three organisational units. Using the data collected from a quantitative survey, this study demonstrates that intangible elements that influence change and innovation initiatives can be measured, understood and managed through decision-making and strategy development to drive future outcomes. The results show that each of the sample organisations has different strengths and weaknesses, each individual unit is unique, and analysis of the current climate highlights areas that may impede change and innovative processes. This is useful tool for managers and management accountants when interpreting performance results and/or developing strategies and future actions.